1995
DOI: 10.1302/0301-620x.77b6.7593116
|View full text |Cite
|
Sign up to set email alerts
|

A new in-vitro model to investigate antibiotic penetration of the intervertebral disc

Abstract: We have studied the ability of a range of antibiotics to penetrate intervertebral disc tissue in vitro, using a mouse disc model. Equilibrium concentrations of antibiotics incorporated into the entire disc were determined by bioassay using a microbial growth-inhibition method. Uptake was significantly higher with positively-charged aminoglycosides compared with negatively-charged penicillins and cephalosporins. Uncharged ciprofloxacin showed an intermediate degree of uptake. Our results support the hypothesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 12 publications
1
32
0
1
Order By: Relevance
“…18 Magnetic resonance imaging at post-discectomy weeks 2 to 3 Isolation of the disc from circulating blood may explain the lack of response to prophylactic antibiotics, and development of intradiscal infection despite minimal bacterial inoculation. The duration of antibiotic prophylaxis should be 24 to 72 hours, 23 although some consider that 24 hours of antibiotic prophylaxis is as beneficial as 48 to 72 hours. [23][24][25][26] Antibiotic prophylaxis expands the golden period.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…18 Magnetic resonance imaging at post-discectomy weeks 2 to 3 Isolation of the disc from circulating blood may explain the lack of response to prophylactic antibiotics, and development of intradiscal infection despite minimal bacterial inoculation. The duration of antibiotic prophylaxis should be 24 to 72 hours, 23 although some consider that 24 hours of antibiotic prophylaxis is as beneficial as 48 to 72 hours. [23][24][25][26] Antibiotic prophylaxis expands the golden period.…”
mentioning
confidence: 99%
“…Positively charged aminoglycosides, gentamicin, and tobramycin penetrate into the disc more significantly than penicillin and cephalosporins do. 23 Gentamicin-containing collagenous sponges placed in the cleared disc space are effective in preventing discitis. 4,5,27 Tobramycin or cephazolin is recommended.…”
mentioning
confidence: 99%
“…Low antibiotic recovery may be attributed to the high binding potential of tissue proteins to anionic β-lactam antibiotics and/or due to the avascular structure of the tissue. Previous animal studies have shown mixed results in regards to cephalosporin diffusion into the disc (Boscardin et al, 1992;Eismont et al, 1987;Lang et al, 1995;Fraser et al, 1989;Thomas et al, 1995). Perhaps this is because many factors infl uence the recovery of cephazolin from tissue samples.…”
Section: Discussionmentioning
confidence: 99%
“…Cephazolin is water soluble, distributed through most body fl uids and tissues (including joints, bone and soft tissues) and continues to be a reasonable choice for prophylaxis. However, timing of administration of cephazolin to prevent infection remains unclear, along with the ability of the antibiotic to penetrate all components of the disc (Eismont et al, 1987;Thomas et al, 1995;Gibson et al, 1987). Despite a better prognosis for the patient, who receives prophylactic antibiotics, attempts to understand the action of antibiotics in the disc are lacking.…”
Section: Amount Of Diluent (µL) X Cephazolin Concentration Measured (mentioning
confidence: 99%
See 1 more Smart Citation